Disney's PETER PAN - Kreider, Karen; Baker, Darrell (Golden Books ; Western Pub. Co. New York, Racine, Wis., 1992)
A retelling of the adventures of Aladdin, who, with the aid of a genie from a magic lamp, fights an evil sorcerer and wins the hand of a beautiful princess